Mutation of the mouse Rad17 gene leads to embryonic lethality and reveals a role in DNA damage-dependent recombination - Budzowska, Magda (2004)
Genetic defects in DNA repair mechanisms and cell cycle checkpoint (CCC) genes result in increased genomic instability and cancer predisposition. Discovery of mammalian homologs of yeast CCC genes suggests conservation of checkpoint mechanisms between yeast and mammals. However, the role of many CCC genes in higher eukaryotes remains elusive. Here, we report that targeted deletion of an N-terminal part of mRad17, the mouse homolog of the Schizosaccharomyces pombe Rad17 checkpoint clamp-loader component, resulted in embryonic lethality during early/mid-gestation. In contrast to mouse embryos, embryonic stem (ES) cells, isolated from mRad17(5′Δ/5′Δ) embryos, produced truncated mRad17 and were viable. These cells displayed hypersensitivity to various DNA-damaging agents. Surprisingly, mRad17(5′Δ/5′Δ) ES cells were able to arrest cell cycle progression upon induction of DNA damage. However, they displayed impaired homologous recombination as evidenced by a strongly reduced gene targeting efficiency. In addition to a possible role in DNA damage-induced CCC, based on sequence homology, our results indicate that mRad17 has a function in DNA damage-dependent recombination that may be responsible for the sensitivity to DNA-damaging agents.